Italian Canyoning Guides: Physiological Profile and Cardiometabolic Demand during Rope Activities - Tommaso Di Libero; Lavinia Falese; Stefano Corrado; Beatrice Tosti; Pierluigi Diotaiuti; Angelo Rodio (MDPI AG, 2024)
Canyoning activities require physical effort, highlighting the importance of maintaining a proper physical fitness. Canyoning guides emerge as key figures, not only to ensure safety during the experience but also to handle unforeseen situations promptly. This study aims to assess the physiological profile of canyoning guides and the cardiorespiratory demands experienced during rope activities by means of oxygen uptake and heart rate measurements. Seventeen canyoning guides (42.6 y ± 10.78; BMI of 24.0 kg/m2 ± 2.95) carried out coordinative and conditional tests. The participants showed good values in strength tests (27.3 cm ± 5.97 and 23.3 rep ± 8.06 in SJ and PUp tests, respectively), while the flexibility of males and females was below and well above the average, respectively. A noteworthy result was observed in the reaction test, in which a better performance was recorded with the non-dominant hand (168.1 ms vs. 202.0 ms). All subjects exhibited a low aerobic capacity by means of an RD test (10.6 ua ± 6.62). During rope activities and emergency/support simulations, metabolic and cardiovascular data indicated that a moderate/high effort was exerted, confirmed by an oxidative stress analysis. In conclusion, this study demonstrated how canyoning guides face significant physical requirements, but their physiological profile regarding aerobic power was not appropriate. Therefore, these findings could offer valuable insights into the development of specific training to ensure an appropriate aerobic fitness to perform canyoning safely.